ChatGPT as Co-Author? AI and Research Ethics - Sharifzadeh, Rahman (Wydział Filozoficzny UAM, 2024)
Should ChatGPT be viewed merely as a supportive tool for writers, or does it qualify as a co-author? As ChatGPT and similar language models are likely to become more prevalent in assisting with academic writing and research, it seems that we will face with two possibilities: an increase in ghostwriting that could finally undermine the integrity of the knowledge system, or the need to theoretical preparation to recognize the role of non-human contributors. Drawing on Actor-Network Theory, this article examines the question of whether this Chatbot meets, in principle, the requirements for co-authorship. Answering this question in affirmative, it delves into philosophical discussions concerning the agency, moral agency, and moral accountability of such technological entities.
Keywords: ChatGPT; authorship; research ethics; Actor-Network Theory